2017
DOI: 10.1155/2017/9562818
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Two Fractional-Order Chaotic Systems via Nonsingular Terminal Fuzzy Sliding Mode Control

Abstract: The synchronization of two fractional-order complex chaotic systems is discussed in this paper. The parameter uncertainty and external disturbance are included in the system model, and the synchronization of the considered chaotic systems is implemented based on the finite-time concept. First, a novel fractional-order nonsingular terminal sliding surface which is suitable for the considered fractional-order systems is proposed. It is proven that once the state trajectories of the system reach the proposed slid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…in which, K D , K P , K I , µ 1 and µ 2 are positive real constants and b ∈ (0, 1) is a positive number. Similar to (16), the condition σ(t) is satisfied for (24), consequently,…”
Section: Design Of the Finite-time Pid Smcmentioning
confidence: 99%
See 2 more Smart Citations
“…in which, K D , K P , K I , µ 1 and µ 2 are positive real constants and b ∈ (0, 1) is a positive number. Similar to (16), the condition σ(t) is satisfied for (24), consequently,…”
Section: Design Of the Finite-time Pid Smcmentioning
confidence: 99%
“…Theorem 4. Consider PID sliding surface (24) and relations (25) and (26). Then, the nonlinear PID sliding surface system ( 27) is finite-time stable, and zero is the asymptotic equilibrium point for (24).…”
Section: Design Of the Finite-time Pid Smcmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been studied in the control and synchronization of time-invariant/varying and SMC chaotic systems [23,24]. In addition, studies have been made on determining the surface of fractional chaotic systems with fuzzy logic [25,26]. In the study, rather than determining the surface, the chattering amplitude was determined by fuzzy logic and synchronization was achieved with the control rule.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the response time of the system and achieving the desired value within a finite time have not been extensively investigated. In Song et al [53], a nonsingular terminal fuzzy SMC approach is suggested for a special category of chaotic systems that are fractional-order systems simultaneously. In Fei et al [51], other fractional-order terminal sliding mode control (FTSMC) technique is applied to synchronize chaotic systems with known upper bound of disturbances.…”
mentioning
confidence: 99%